Cliff evolution and late Holocene relative sea level change along the Otranto coast (Salento peninsula, southern Apulia, Italy). (December 2016) - Sansò, P.; Gianfreda, F.; Leucci, G.; Mastronuzzi, G.
Abstract: The geomorphological analysis of cliff coast stretching to the north of Otranto (southern Apulia, Italy) was integrated by penetrometer tests and geophysical survey aiming to reconstruct its late Holocene evolution. In particular, the study focuses on the inactive cliff of Torre dell'Orso inlet which hosts a 150 m - wide beach and a high dune belt. The survey detected the cliff/wave-cut platform junction at about 3.8 m below m.s.l. The platform is covered by a dune/beach sedimentary cover about 7 m thick. The collated data along with the available local sea level curves allow to reconstruct Otranto's cliff evolution as the result of late Holocene relative sea-level change due to eustasy and land motions. Cliff development was promoted by a sea still-stand level at about 3.5 m below present mean sea level occurred between 3400 and 2400 years BP. A rapid sea level rise followed so that several tracts of cliffs were partly drowned becoming plunging cliffs. Cliff recession followed fast sea level rise only along preferential groundwater flow lines where hyperkarst process, due to fresh/salt water mixing, produced deep notches in the calcarenite bedrock inducing rock falls and cliff recession. This process is responsible for the indentation of present shoreline. Finally, during the last four centuries a wide beach and a high dune belt formed at Torre dell'Orso inlet as a result of the increased carry load of Ofanto River, so that the plunging cliff has been separated by shoreline becoming an inactive cliff. Finally, comparing the reconstructed local sea level history during the late Holocene with the available sea level curves produced by glacio-hydro-isostastic models, a yo-yoing land motion with a period of about 4500 years and amplitude of about 2 m can be inferred for the eastern coast of Salento peninsula.